Interferometric Study of Ionospheric Plasma Irregularities in Regions of Phase Scintillations and HF Backscatter. Issue 12 (16th June 2022) - Spicher, Andres; LaBelle, James; Bonnell, John W.; Roglans, Roger; Moser, Chrystal; Fuselier, Stephen A.; Bounds, Scott; Clausen, Lasse B. N.; Di Mare, Francesca; Feltman, Connor A.; Jin, Yaqi; Kletzing, Craig; et al.
Abstract: We investigate the nature of small‐scale irregularities observed in the cusp by the Twin Rockets to Investigate Cusp Electrodynamics‐2 (TRICE‐2) in regions of enhanced phase scintillations and high‐frequency coherent radar backscatter. We take advantage of the fact that the irregularities were detected by spatially separated probes, and present an interferometric analysis of both the observed electron density and electric field fluctuations. We provide evidence that fluctuations spanning a few decameters to about a meter have low phase velocity in the plasma reference frame and are nondispersive, confirming that decameter‐scale irregularities follow the E × B velocity. Furthermore, we show that these "spatial" structures are intermittent and prominent outside of regions with strongest precipitation. The observations are then discussed in the context of possible mechanisms for irregularity creation. Plain Language Summary: Ionospheric plasma are known to be highly irregular, with fluctuations evolving both in space and time. Irregular structures can reach hundreds of kilometers to a few meters and, despite being common and having space weather impacts, the details of their source(s) and behavior are still unclear, especially at smaller scales. In this work, we investigate small‐scale plasma density and electric field fluctuations observed by a sounding rocket where ground‐based instruments also detected irregularities. To circumvent ambiguities of interpreting measurements made by single probes, we take advantage of the fact that the fluctuations were detected by spatially separated probes and use multi‐point analysis techniques to separate the spatial and temporal scales of the observed structures. The analysis allows to estimate the phase velocities and wavelengths of the fluctuations and reveals spatial irregularities from tens of meters to a meter, that is, irregularities that are slow in the plasma frame. Additionally, we show that these small‐scale structures are concentrated outside of regions where most electrons are precipitating downward along the Earth's magnetic field and discuss the observations in the context of irregularity creation. Altogether, this study provides new insights into the sources and behavior of high‐latitude ionospheric irregularities. Key Points: The phase velocity and wavelength of coexisting ionospheric cusp density and electric field fluctuations is determined using interferometry In‐situ confirmation of decameter‐–meter‐scale density and electric field fluctuations having low phase velocity in the plasma frame Intermittent decameter‐scale fluctuations coincide with larger‐scale density variations outside of enhanced precipitation regions